2018
DOI: 10.1002/cam4.1502
|View full text |Cite
|
Sign up to set email alerts
|

Programmed death‐ligand 1 expression in gastric cancer: correlation with mismatch repair deficiency and HER2‐negative status

Abstract: Gastric cancer (GC) is one of the most common malignancies. Immunotherapy is a promising targeted treatment. The immune regulatory programmed death‐1 (PD‐1)/programmed death‐ligand 1 (PD‐L1) axis has been used as a checkpoint target for immunotherapy. Currently, considerable discrepancies exist concerning the expression status of PD‐L1 and its prognostic value in GC. We aimed to evaluate the expression rates of PD‐L1 in GC, and further assess its relationship with mismatch repair (MMR), and human epidermal gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
29
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 33 publications
6
29
2
2
Order By: Relevance
“…In our study, PD-L1 expression in immune and tumor cells was observed in 17% of AN gastric cancer patients. A PD-L1 combined positive score greater than 1 was significantly correlated with MMR deficient patients, similar to previous studies in breast [65], colorectal [66], gastric [67], and esophageal cancers [68,69]. Moreover, in gastric cancer, it has been well-known that PD-L1+ tumors frequently have PIK3CA mutations, which are also strongly associated with MSI-high and EBV+ tumors [13,59,70,71], as we observed in our cohort.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, PD-L1 expression in immune and tumor cells was observed in 17% of AN gastric cancer patients. A PD-L1 combined positive score greater than 1 was significantly correlated with MMR deficient patients, similar to previous studies in breast [65], colorectal [66], gastric [67], and esophageal cancers [68,69]. Moreover, in gastric cancer, it has been well-known that PD-L1+ tumors frequently have PIK3CA mutations, which are also strongly associated with MSI-high and EBV+ tumors [13,59,70,71], as we observed in our cohort.…”
Section: Discussionsupporting
confidence: 91%
“…In many studies regarding ICIs, biomarkers have been investigated. The expression of PD-L1 or PD-L2 [ 15 ], mutation burden [ 16 ], dMMR [ 17 ] are said to be associated with the efficacy of ICIs. Furthermore, the expressions of PD-L1 and PD-L2 are associated with the response to ICIs [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of PD-L1 or PD-L2 [ 15 ], mutation burden [ 16 ], dMMR [ 17 ] are said to be associated with the efficacy of ICIs. Furthermore, the expressions of PD-L1 and PD-L2 are associated with the response to ICIs [ 15 ]. In patients with lung cancer, pembrolizumab was more effective for higher expression of PD-L1 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, PD-L1 expression is associated with clinical response in patients with non-squamous non-small cell lung cancer [22]. PD-L1 positivity is observed in up to 65% of GC specimens [20], and even though it is widely associated with negative features, such as tumour size, lymph node metastasis and depth of invasion, there is no consensus on the role of PD-L1 expression as a prognostic biomarker in GC [23]. While the KEYNOTE-061 trial confirmed a better outcome with pembrolizumab in patients with PD-L1-positive tumours [13] data from the JAVELIN Gastric 300 and ATTRACTION-2 trials did not support the concept of PD-L1 positivity as a predictive response marker to ICIs [14,15].…”
Section: Discussionmentioning
confidence: 99%